(untitled) (Medicine Today, 2019)
Introduction: Perineal tear (PT) is the most frequently occurring injury during vaginal birth. Striae gravidarum (SG) is a reflecting marker of connective tissue elasticity. This study aimed to assess SG score and to predict the likelihood of PT during childbirth. Materials & Methods: This was a cross-sectional study done at Sir Salimullah Medical College & Mitford Hospital. Initially, all pregnant women admitted for vaginal delivery were enrolled but who subsequently needed lower segment caesarean section were excluded. Finally, 189 patients who gave vaginal birth were included. SG score was assessed using the Atwal numerical scoring system. The association was examined between PT as the outcome measure, defined by tears or lacerations and the total striae score (TSS) obtained at abdomen, hips, buttocks and breasts. Results: More than half of study patients developed PT. Majority belonged to moderate striae group. Significant correlation was found between PT and TSS. Moderate and severe striae had significantly increased prevalence of PT as compared to mild striae (43.4% vs. 11.6%). Patients who were given episiotomy in moderate and severe striae group had less PT. Weight gain during pregnancy and TSS were significantly associated with a higher incidence of PT. Conclusion: A woman’s SG score in general is a useful clinical predictor of the risk for PT during childbirth. Selective episiotomy in patients with moderate and severe striae can reduce the incidence of PT. SG score can be used as a simple and noninvasive tool by all categories of health personnel to better define women at risk for PT. Medicine Today 2019 Vol.31(2): 64-67